Investigating the Campylobacter jejuni Transcriptional Response to Host Intestinal Extracts Reveals the Involvement of a Widely Conserved Iron Uptake System - Martha M. Liu (American Society for Microbiology, 2018)
ABSTRACT Campylobacter jejuni is a pathogenic bacterium that causes gastroenteritis in humans yet is a widespread commensal in wild and domestic animals, particularly poultry. Using RNA sequencing, we assessed C. jejuni transcriptional responses to medium supplemented with human fecal versus chicken cecal extracts and in extract-supplemented medium versus medium alone. C. jejuni exposed to extracts had altered expression of 40 genes related to iron uptake, metabolism, chemotaxis, energy production, and osmotic stress response. In human fecal versus chicken cecal extracts, C. jejuni displayed higher expression of genes involved in respiration (fdhTU) and in known or putative iron uptake systems (cfbpA, ceuB, chuC, and CJJ81176_1649–1655 [here designated 1649–1655]). The 1649–1655 genes and downstream overlapping gene 1656 were investigated further. Uncharacterized homologues of this system were identified in 33 diverse bacterial species representing 6 different phyla, 21 of which are associated with human disease. The 1649 and 1650 (p19) genes encode an iron transporter and a periplasmic iron binding protein, respectively; however, the role of the downstream 1651–1656 genes was unknown. A Δ1651–1656 deletion strain had an iron-sensitive phenotype, consistent with a previously characterized Δp19 mutant, and showed reduced growth in acidic medium, increased sensitivity to streptomycin, and higher resistance to H2O2 stress. In iron-restricted medium, the 1651–1656 and p19 genes were required for optimal growth when using human fecal extracts as an iron source. Collectively, this implicates a function for the 1649–1656 gene cluster in C. jejuni iron scavenging and stress survival in the human intestinal environment. IMPORTANCE Direct comparative studies of C. jejuni infection of a zoonotic commensal host and a disease-susceptible host are crucial to understanding the causes of infection outcome in humans. These studies are hampered by the lack of a disease-susceptible animal model reliably displaying a similar pathology to human campylobacteriosis. In this work, we compared the phenotypic and transcriptional responses of C. jejuni to intestinal compositions of humans (disease-susceptible host) and chickens (zoonotic host) by using human fecal and chicken cecal extracts. The mammalian gut is a complex and dynamic system containing thousands of metabolites that contribute to host health and modulate pathogen activity. We identified C. jejuni genes more highly expressed during exposure to human fecal extracts in comparison to chicken cecal extracts and differentially expressed in extracts compared with medium alone, and targeted one specific iron uptake system for further molecular, genetic, and phenotypic study.